Zinc transformations in a rice soil irrigated with sodic wafer - MINHAS, NEETU; CHHIBBA, I M (The Indian Journal of Agricultural Sciences, 2013)
Transformation of native and applied Zn in an alkaline calcareous loam soil transplanted with rice (Oryza sativa L.) and irrigated with water having varying levels of sodicity (RSC 0,5, 10 and 20 me/litre) was studied in a screenhouse experiment. Of the various fractions, water soluble plus exchangeable Zn (WSE-Zn), amorphous oxides and carbonates bound Zn (AMOX+CBT-Zn) and Zn bound by crystalline oxides (CRYOX-Zn) experienced an increase, whereas the complexed Zn (COM-Zn), organically bound Z11 (OO-Zn) and residual Zn (RES-Zn) registered a decrease with increasing water sodicity irrespective of the sampling stage. Residual Zn (RES-Zn) formed the most dominant fraction of Zn. All the fractions appeared to be in a dynamic equilibrium as revealed by significant correlations among them.